Microwave-assisted synthesis of cyclodextrin polyurethanes. (20th November 2015) - Biswas, Atanu; Appell, Michael; Liu, Zengshe; Cheng, H.N.
Highlights: Microwave-assisted method has been developed to produce cyclodextrin/polyurethanes. This method saves energy, time, and yet improves the product yield. Products were fully characterized with NMR spectroscopy. Possible applications include the removal of toxic compounds from the environment. ABSTRACT: Cyclodextrin (CD) has often been incorporated into polyurethanes in order to facilitate its use in encapsulation or removal of organic species for various applications. In this work a microwave-assisted method has been developed to produce polyurethanes consisting of α-, β-, and γ-CD and three common diisocyanates. As compared to conventional heating, this new synthetic method saves energy, significantly reduces reaction time, and gets similar or improved yield. The reaction products have been fully characterized with 13 C, 1 H, and two-dimensional NMR spectroscopy. With suitable stoichiometry of starting CD and diisocyanate, the resulting CD polyurethane is organic-soluble and water-insoluble and is shown to remove Nile red dye and phenol from water. Possible applications include the removal of undesirable materials from process streams, toxic compounds from the environment, and encapsulation of color or fragrance molecules.